Teacher Strategies in the Potential Optimization of Children with Special Needs in Elementary School - Herlina Febriyani; Suyatno; Muhammad Zuhaery (Jurnal Ilmiah Sekolah Dasar, 2024)
The implementation of inclusive education in Indonesia is facing various challenges, including issues with access to education, discriminatory treatment, and a lack of competent resources to implement inclusive education. Strategies employed by teachers to optimize the potential of children with special needs in elementary school were discussed. Therefore, this research aimed to ascertain information regarding teachers' strategies in optimizing the potential of inclusive students, despite the constraints posed by competent teachers, curriculum adaptability, and the quality and competency of teachers without special education background. Furthermore, this research used qualitative methods and a case study approach. Data collection was carried out by observing and interviewing school principals, class teachers, subject teachers, and students with special needs in elementary schools in Bengkalis Regency, Riau. The research concluded that strategies used by teachers in adapting to these limitations are crucial in providing optimal services to inclusive students. In some aspects, teachers' knowledge of well-established methods such as IEP and TEACCH cannot be fully implemented in school. However, every step and process was carried out with an method adjusted to the capabilities of school. These steps included assessment processes, communication with parents, development of educational goals, learning methods and procedures, learning materials, timeframes, achievement targets, and evaluation. Additionally, the availability of special support teachers was an essential requirement to effectively manage the inclusive education program.